Aedes aegypti D7 long salivary proteins modulate blood feeding and parasite infection - Ines Martin-Martin; Bianca Burini Kojin; Azadeh Aryan; Adeline E. Williams; Alvaro Molina-Cruz; Paola Carolina Valenzuela-Leon; Gaurav Shrivastava; Karina Botello; Mahnaz Minai; Zach N. Adelman; Eric Calvo (mBio, 2023)
ABSTRACTMosquito saliva facilitates blood meal acquisition through pharmacologically active compounds that prevent host hemostasis and immune responses. Here, we generated two knockout (KO) mosquito lines by CRISPR/Cas9 to functionally characterize D7L1 and D7L2, two abundantly expressed salivary proteins from the yellow fever mosquito vector Aedes aegypti. The D7s bind and scavenge biogenic amines and eicosanoids involved in hemostasis at the bite site. The absence of D7 proteins in the salivary glands of KO mosquitoes was confirmed by mass spectrometry, enzyme-linked immunosorbent assay, and fluorescence microscopy of the salivary glands with specific antibodies. D7-KO mosquitoes had longer probing times than parental wildtypes. The differences in probing time were abolished when mutant mice resistant to inflammatory insults were used. These results confirmed the role of D7 proteins as leukotriene scavengers in vivo. We also investigated the role of D7 salivary proteins in Plasmodium gallinaceum infection and transmission. Both KO lines had significantly fewer oocysts per midgut. We hypothesize that the absence of D7 proteins in the midgut of KO mosquitoes might be responsible for creating a harsh environment for the parasite. The information generated by this work highlights the biological functionality of salivary gene products in blood feeding and pathogen infection.IMPORTANCEDuring blood feeding, mosquitoes inject saliva into the host skin, preventing hemostasis and inflammatory responses. D7 proteins are among the most abundant components of the saliva of blood-feeding arthropods. Aedes aegypti, the vector of yellow fever and dengue, expresses two D7 long-form salivary proteins: D7L1 and D7L2. These proteins bind and counteract hemostatic agonists such as biogenic amines and leukotrienes. D7L1 and D7L2 knockout mosquitoes showed prolonged probing times and carried significantly less Plasmodium gallinaceum oocysts per midgut than wild-type mosquitoes. We hypothesize that reingested D7s play a vital role in the midgut microenvironment with important consequences for pathogen infection and transmission.